Ecological School Garden - Integrated Environmental Education Model: A Case Study in Hanoi - Huong, Bui Thi Thanh; Mai Chi, Phi (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 2DO - 10.25073/2588-1094/vnuees.5503, 2026)
Rapid urbanization in Hanoi is shrinking green spaces and intensifying nature deficit disorder among school-age children, undermining mental health and ecological awareness. Vietnam's General Education Curriculum 2018 and COP26 commitments create urgent demand for integrated environmental education in schools, yet evidence-based models remain scarce. This study examines eco-school gardens as integrated environmental education environments across three schools representing distinct governance and socio-ecological contexts in Hanoi: Genesis School (private, urban circular economy), Hermann Gmeiner School (semi-public, project-based learning), and the Ethnic Boarding High School in Ba Vi (public, indigenous knowledge conservation). Using a mixed-methods multiple case study design combining participant observation, focus group consultations, and secondary data analysis, the research applies five theoretical frameworks - the Gaia hypothesis, human environment systems, systems thinking, Bourdieu's Cultural Capital/Habitus, and Kolb's Experiential Learning Cycle to evaluate educational outcomes across sites. Findings demonstrate that Permaculture designed eco-school gardens can simultaneously deliver STEAM interdisciplinary education, green career guidance, and indigenous knowledge preservation, with effectiveness shaped by local socio-ecological context rather than a-one-size-fits- all approach. The study proposes a three-component framework: Permaculture-based spatial design, an integrated Green and Digital curriculum encompassing 8 ecolifestyle stations and 10 career- oriented projects, and multi-stakeholder policy recommendations aligned with Vietnam's Net Zero 2050 commitment.